Pengembangan Media Belajar Audio Visual Pelajaran Ilmu Pengetahuan Sosial Geografi Materi Angkatan Kerja Dan Tenaga Kerja Di SMP Negeri Sawit II Boyolali - SAPUTRO, RUDY, Drs. Dahroni, M.Si (2015)
Based on data from the field orientation conventional learning students who do not use the media in learning seem less exciting and boring, as well as ways of human thinking from the concrete towards abstract thinking makes use of media in learning will help the understanding of the material provided to the students. The purpose of this research is to develop instructional video media can be used to help the understanding of students on the material Labor Force and Employment, and knowing instructional video media is more effective than conventional methods. This research method using experimental research methods, the research sought treatment effectiveness of specific variables on other variables in controlled conditions, which is a class of experimental research with the treatment of pre - post test controlled group. There is an experimental class that is using video media strategy pembelajran and grade control using conventional methods. The results show the value of pre-test control class that is 49.16 and the value of pre-test experimental classes, namely 32.69. Pre-test values ​​higher than the control group in the experimental class with a difference of 16.47. Results of the average value of the post test and control classes 39.67, while the average value of post test experimental class 76.43. Increased to 36.76, while the KKM specified is 75. The conclusion of this study is the learning objectives in learning materials and labor work force can be achieved and the development of instructional video media workforce and labor can increase students' understanding.